2016
DOI: 10.5152/tao.2015.1359
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid Vegetation in Children with Allergic Rhinitis

Abstract: Objective: Pediatric patients with nasal obstruction due to adenoid vegetation (AV) can also encounter allergic rhinitis (AR) as a comorbidity. The aim of the study was to estimate the incidence of mite sensitization and its effect on adenoid size in children who underwent adenoidectomy.Methods: This prospective randomized study conducted between August and September 2014 included 84 children. Skin Prick Test (SPT) for inhalant allergens was preoperatively applied to all children who underwent adenoidectomy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…The adenoid / nasopharynx ratio was significantly higher in the non-allergic group. Bozkurt et al ( 360 ) performed skin prick test on the patients who had adenoidectomy, and compared the removed adenoid’s volume, VAS scores, and adenoid size on flexible nasopharyngoscopic examination between the prick test positive (32 patients) and negative (52 patients) groups. They reported significantly higher adenoid volume in patients with AR.…”
Section: Diagnosis Of Allergic Rhinitismentioning
confidence: 99%
See 1 more Smart Citation
“…The adenoid / nasopharynx ratio was significantly higher in the non-allergic group. Bozkurt et al ( 360 ) performed skin prick test on the patients who had adenoidectomy, and compared the removed adenoid’s volume, VAS scores, and adenoid size on flexible nasopharyngoscopic examination between the prick test positive (32 patients) and negative (52 patients) groups. They reported significantly higher adenoid volume in patients with AR.…”
Section: Diagnosis Of Allergic Rhinitismentioning
confidence: 99%
“…Hypertrophic adenoids may get smaller and the volume of the nasal cavity may increase with the use of NCS ( 365 , 433 - 435 ). Comparative studies showed that NCS are more effective than oral antihistamines in the control of nasal symptoms, while there was no significant difference between these two agents for ocular symptoms.…”
Section: Treatment Of Allergic Rhinitismentioning
confidence: 99%
“…The portal position of adenoid in the upper respiratory tract makes it an accordant reservoir of virus and bacteria causing recurrent infections which ends up with lymphoid hyperplasia. Allergic inflammation is another cause of adenoid enlargement in which the adenoid tissue will contain numerous IgE-positive mast cells [1,3,4] . Chronic nasal obstruction due to adenoid enlargement is one of the most common children's complaints that may be associated with chronic sinusitis and recurrent otitis media, therefore adenoidectomy is considered as the most surgical procedure performed in pediatric age group [5] .…”
Section: Introductionmentioning
confidence: 99%
“…They require more expensive equipment than PNIF with nearly the same ability to estimate nasal airflow, which is an objective, non-specific measurement for nasal obstruction and response to treatment regardless of the etiology. Recently, the visual analog scale (VAS) enables an uncomplicated, rapid, and reproducible evaluation of nasal symptom severity and has been used for AH before [5].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the visual analog scale (VAS) enables an uncomplicated, rapid, and reproducible evaluation of nasal symptom severity and has been used for AH before [ 5 ].…”
Section: Introductionmentioning
confidence: 99%